1994
DOI: 10.1111/j.1439-037x.1994.tb00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Deficiency Affects the Early Development of Wheat Plants

Abstract: The effect of phosphorus nutrition on the development of wheat plants, was studied. Phosphorus deficiency increased the duration of the phyllochron when the concentration in shoots was less than 0.8 %. Phosphorus concentration in shoots appeared to be a good indicator of the effect of plant phosphorus status on wheat development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…1). Delayed development appears to be a consequence of low P availability because this response was also reported for lupine, wheat, and Arabidopsis ( Rodriguez et al, 1994; Ma et al, 2002; Nord and Lynch , 2008). For example, Nord and Lynch (2008) found that low P availability delayed bolting and maturity in seven genotypes of Arabidopsis thaliana .…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…1). Delayed development appears to be a consequence of low P availability because this response was also reported for lupine, wheat, and Arabidopsis ( Rodriguez et al, 1994; Ma et al, 2002; Nord and Lynch , 2008). For example, Nord and Lynch (2008) found that low P availability delayed bolting and maturity in seven genotypes of Arabidopsis thaliana .…”
Section: Discussionmentioning
confidence: 64%
“…For example, Nord and Lynch (2008) found that low P availability delayed bolting and maturity in seven genotypes of Arabidopsis thaliana . It has been suggested that the reason for the delayed leaf maturity was a slower growth rate caused by low P supply ( Rodriguez et al, 1994; Nord and Lynch , 2008), but biochemical and molecular studies support that P deficiency massively impedes growth‐regulating phytohormones ( Zhang et al, 2014). Therefore, it is currently not clear whether the low P levels affected growth directly or indirectly via phytohormones.…”
Section: Discussionmentioning
confidence: 99%
“…3a and b). Net export of dry matter from leaves and stems was observed after 90 DAS, whereas net export of P started at 67 DAS (a) (2) 10.5~~ (964.7 degree days). Net export of P and dry matter starte-d earlier in high-P plants than in low-P plants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Rodriguez et al (2) found that the duration of the phyllochron on wheat plants growing in two different soils was inversely related to the concentration of P in the shoots early during plant development. Hajabbasi and Schumacher (18) also showed that the addition of P decreased the time to reach a given developmental stage for two genotypes of maize.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation